Metaheuristic Algorithms for the Vehicle Routing Problem - Trinh Viet, Son (2025)
This thesis addresses the critical challenge of operational efficiency in logistics by focusing on a rich and highly constrained Vehicle Routing Problem (VRP). The prob- lem involves optimizing routes for a heterogeneous vehicle fleet subject to multiple, interdependent constraints, including Fixed Fleet limits, Dual Capacity restrictions (Weight and Pallets), Time Windows, and specialized geographical access barriers (City Center restrictions). Due to the substantial scale and complexity of the problem instance, traditional exact solution methods are unsuitable for timely implementation. This research, therefore, proposes and validates a highly tailored solution framework based on the Adaptive Large Neighborhood Search (ALNS) metaheuristic. Computational experiments demonstrate that the ALNS framework is highly scalable and effective at navigating the constrained search space.